Dollar dominance is here to stay for the foreseeable future: The real issue for the global economy is how and why - Steven Kamin; Mark Sobel (American Enterprise Institute (AEI), 2024)
In this paper, we examine the prospects for, and implications of, the dollar's continued pivotal role in the international financial system. We find, first, that the dollar remains dominant by a wide margin and will likely retain its dominance for the foreseeable future-none of the other contenders possess the liquidity, safety, and investor protections that are required for the currency world's top job. We then evaluate the benefits that the United States derives from the dollar's dominance. On the geopolitical side, the United States derives material benefits from the dollar's dominance, as it makes sanctions against bad actors around the world more effective. But contrary to the criticisms that the United States enjoys an "exorbitant privilege," we doubt that the economic benefits of the dominant dollar for the United States are very large or that this dominance imposes large costs on our trading partners. In fact, the widespread use of the dollar has likely promoted global trade, international investment, and economic growth by providing a common unit of account, means of exchange, and store of value. We conclude by noting that the direst threat to the dollar emerges from the United States itself, with partisan divisions, political dysfunction, and the resultant inability to cope with the nation's challenges posing important risks to the country's economic and financial prospects. Were those risks to materialize, the loss of the dollar's dominance would be the least of our problems.
Keywords: 330; Reservewährung; US-Dollar; Internationales Finanzsystem; Geopolitik; Wirkungsanalyse; Welt